COOKIES SUBSTITUSI TEPUNG BAYAM MERAH DAN TEPUNG KACANG TOLO SEBAGAI MAKANAN TAMBAHAN REMAJA PUTRI ANEMIA Cookies substitution of red spinach flour and cowpea flour as complementary food of anemic adolescent girls - Suriani Rauf; Manjilala Manjilala; Nursalim Nursalim; Mustamin Mustamin; Nur Azisah (Media Gizi Pangan, 2022)
ABSTRACT Adolescent girls are one of the age groups that are vulnerable to nutritional problems, namely anemia. Anemia in adolescent girls must be overcome because it can affect their lives in the future. The habit of eating snacks can be an opportunity in presenting additional foods that are high in iron. Additional food can be given in the form of cookies. Cookies can be made from red spinach flour and tolo bean flour which are high in iron content. This study aims to determine the acceptability and iron content of cookies substituted with red spinach flour and tolo bean flour as additional food for anemic adolescent girls. This type of research is experimental with One Shot Case Study research design. The panelists in this study were 30 female students. The data from the acceptance results were processed with a computer program and analyzed using the Kruskall-Wallis test. Analysis of iron content based on laboratory test results using the AAS (Atomic Absorbtion Spectrophotometry) method. The data is presented in tabular form and accompanied by an explanation in the form of a narrative. The results showed that the most preferred acceptability of cookies substituted with red spinach flour and peanut flour from the aspect of color, aroma, texture, and taste was cookies with a concentration of 10:10%. The results of laboratory tests showed that the iron content in cookies at a concentration of 10:10% was 5.250 mg/100 g cookies. It is recommended to test the content of other nutrients besides iron and shelf life to determine the resistance of cookies substituted with red spinach flour and tolo bean flour. Keywords : Cookies, Acceptance, Iron, Red Spinach Flour, Cowpea Flour ABSTRAK Remaja putri merupakan salah satu kelompok usia yang rentan terhadap masalah gizi yaitu anemia. Anemia pada remaja putri harus diatasi karena dapat berpengaruh pada kehidupan di masa mendatang. Kebiasaan mengonsumsi cemilan dapat menjadi peluang dalam menghadirkan makanan tambahan yang tinggi zat besi. Pemberian makanan tambahan dapat dilakukan dalam bentuk cookies. Cookies dapat dibuat dari tepung bayam merah dan tepung kacang tolo yang tinggi kandungan zat besi. Penelitian ini bertujuan untuk mengetahui daya terima dan kandungan zat besi cookies subsitusi tepung bayam merah dan tepung kacang tolo sebagai makanan tambahan remaja putri anemia. Jenis penelitian ini adalah eksperimental dengan desain penelitian One Shot Case Study. Panelis dalam penelitian ini sebanyak 30 orang mahasiswi. Data dari hasil daya terima diolah dengan program komputer dan di analisis menggunakan uji kruskall-wallis. Analisis kandungan zat besi berdasarkan hasil uji laboratorium menggunakan metode AAS (Atomic Absorbtion Spektrophotometry). Data disajikan dalam bentuk tabel dan disertai dengan penjelasan dalam bentuk narasi. Hasil penelitian menunjukkan bahwa daya terima cookies subsitusi tepung bayam merah dan tepung kacang tolo yang paling disukai dari aspek warna, aroma, tekstur, dan rasa adalah cookies konsentrasi 10:10%. Hasil uji laboratorium menunjukkan bahwa kandungan zat besi pada cookies konsentrasi 10:10% adalah 5,250 mg/100 g cookies. Disarankan melakukan uji kandungan zat gizi lain selain zat besi dan umur daya simpan untuk mengetahui ketahanan cookies substitusi tepung bayam merah dan tepung kacang tolo. Kata kunci : Cookies, Daya Terima, Zat Besi, Tepung Bayam Merah, Tepung Kacang Tolo